ISLAMIC GOVERNANCE MATURITY MODEL: KERANGKA EVALUASI TATA KELOLA ORGANISASI PERGURUAN TINGGI ISLAM - Moh Ali; Encep Darisman; Sasikirana Rizky Ramadhania (Ar Rasyiid: Journal of Islamic Studies, 2026)
The governance of Islamic universities in Indonesia and Muslim-majority countries is still dominated by the Good University Governance (GUG) framework, while Islamic values have generally not been operationalized as a measurable governance component. This condition creates a gap between the ideals of value-based governance and the practice of quality evaluation. This article aims to formulate the Islamic Governance Maturity Model (IGMM), which is an evaluation framework that integrates modern governance principles with maqāṣid al-syarī'ah. The research uses a qualitative approach through systematic literature research and design science logic. The results of the study produced seven main dimensions, namely prophetic leadership, transparency, accountability, participation (syūrā), justice ('adl), sustainable quality, and spiritual governance, which are mapped into five levels of maturity: Unorganized, Reactive, Systematized, Integrated, and Transformative-Maqāṣid. The novelty of this model lies in the operationalization of spiritual values into measurable indicators that support internal evaluation, external assessment, quality assurance, accreditation, and require empirical validation on various typologies of Isla universities.